Spontaneous uterine rupture after abdominal myomectomy at the gestational age of 20 weeks in pregnancy: A case report - Hamideh Pakniat; Nasrin Soofizadeh; Marzieh Beigom Khezri (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Uterine rupture in pregnancy is rare and often could be life threatening and catastrophic. Myomectomy is one of very common surgeries in gynecology, performed as the vaginal, abdominal and laparoscopic surgeries. Pregnancies occured after abdominal and laparoscopic myomectomy are high risk for uterine rapture. Case: Patient was a 28 Years old female, pregnant woman at the 20 wks of gestational age with abdominal pain and a history of abdominal myomectomy 6 yrs ago. Uterus was ruptured and fetus in amniotic sac was found in abdominal cavity. Conclusion: Early diagnosis of uterine rupture after myomectomy can save patients from death